Corrosion Resistance Properties of Aluminum Coating Applied by Arc Thermal Metal Spray in SAE J2334 Solution with Exposure Periods - Lee, H.; Singh, J.; Ismail, Mohamed A.; Bhattacharya, C. (MDPI AG, 2016)
Arc thermal metal spray coating provides excellent corrosion, erosion and wear resistance to steel substrates. This paper incorporates some results of aluminum coating applied by this method on plain carbon steel. Thereafter, coated panels were exposed to an environment known to form stable corrosion products with aluminum. The coated panels were immersed in Society of Automotive Engineers (SAE) J2334 for different periods of time. This solution consists of an aqueous solution of NaCl, CaCl2 and NaHCO3. Various electrochemical techniques, i.e., corrosion potential-time, electrochemical impedance spectroscopy (EIS) and the potentiodynamic were used to determine the performance of stimulants in improving the properties of the coating. EIS studies revealed the kinetics and mechanism of corrosion and potentiodynamic attributed the formation of a passive film, which stifles the penetration of aggressive ions towards the substrate. The corrosion products that formed on the coating surface, identified using Raman spectroscopy, were Dawsonite (NaAlCO3(OH)2) and Al(OH)3. These compounds of aluminum are very sparingly soluble in aqueous solution and protect the substrate from pitting and uniform corrosion. The morphology and composition of corrosion products determined by scanning electron microscopy and energy dispersive X-ray analyses indicated that the environment plays a decisive role in improving the corrosion resistance of aluminum coating.